Highly-Accurate, Implantable Micromanipulator for Single Neuron Recordings - Yang, Sungwook; Lee, Semin; Park, Kitae; Kim, Jinseok; Cho, Jeiwon; Shin, Hee-Sup; Yoon, Eui-Sung (2010 IEEE INTERNATIONAL CONFERENCE ON ROBOTICS AND AUTOMATION (ICRA), 2010)
A precise and implantable micromanipulator is presented for automatically advancing electrodes during single unit recordings in freely-behaving animals. The modular design and enhanced clamping mechanism with simple mechanical components are designed to provide reliable linear motion using a piezo motor with a stroke of 3 mm. To be specific, a closed loop control system, based on the position feedback from a magnetoresistive (MR) sensor, was implemented to overcome the non-linear characteristics of the piezo motor and to locate electrodes precisely at the targeted position with the accuracy of 1 mu m, even under load. The weight of the micromanipulator is only 0.84 g when it is fully assembled with the MR sensor, PCBs, and connectors. In addition, a protective cover is employed to prevent breakage during semi-chronic recording. The positioning performance of the micromanipulator was tested at various loading conditions using various control methods. Finally, the activities of a single unit were isolated successfully using small step adjustments, such as 1 to 5 mu m, in freely-moving mice.